A study on urban farming in highly urbanized areas the case of the Joy of Urban Farming program of Quezon City, Metro Manila - Alumasa Sheila Uside (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
Understanding the role of urban farming in highly urbanized cities in the livelihood generation of the urban residents and in an urban community at large helps to realize the relevance of the sector in urban poverty alleviation and to give urban development policy reforms formulation.The study was undertaken in Quezon City where the Joy of Urban Farming Program was chosen as a case study. The program is implemented in several barangays of Quezon City from District 1 to District 6. The study assessed whether urban farming contributed to livelihood generation among its inner-city poor. The study assumed that understanding and optimizing the role of urban farming in urban systems help urban dwellers improve their livelihoods. It also identified the major urban agricultural production systems in Quezon City, and their roles in livelihood generation of urban farmer households, urban poverty alleviation and sustainable urban farming. Based on the results of the household survey, the Joy of Urban Farming Program has improved the livelihood of the beneficiaries through attainment of food security, availability of alternative source of income and job opportunities as well as improvement of their human capital. However, the study revealed that the urban farmers have not fully benefited from the food garden in terms of access to land in the highly urbanized city. They have been able to innovatively use limited spaces such as vertical and rooftop garden as well as utilize vacant lands. The study showed that the Joy of Urban Farming Program has sustainability concern since the program only receives financial support from the office of the Vice Mayor. Its sustainability is a consideration when it comes to the change of office or the lack of political will from newly elected local executive. It is recommended that the City Development Planning Office should incorporate urban farming into its open space development strategies. In line with this, there is also need for government support to ensure sustainability of the program through provision of land for agricultural production. This will encourage urban farming in other parts of Quezon City.